Normalization of serum immunoglobulin G levels is associated with improved transplant-free survival in patients with autoimmune hepatitis. Issue 7 (July 2020) - Gerussi, Alessio; Halliday, Neil; Saffioti, Francesca; Bernasconi, Davide Paolo; Roccarina, Davide; Marshall, Aileen; Thorburn, Douglas
Abstract: Background: There is limited evidence linking achievement of biochemical response with outcomes in Autoimmune Hepatitis (AIH), and it is unclear whether normalization of serum immunoglobulin G (IgG) levels influences prognosis. Aims: We aimed to investigate factors associated with death or liver transplantation in patients affected by AIH. Methods: We undertook a retrospective analysis of all AIH patients attending a tertiary liver unit since 1980. Patients not meeting established diagnostic criteria for AIH or with a follow-up shorter than 18 months were excluded. Results: 107 patients meeting inclusion criteria were included in the study. Mean age at diagnosis was 44 years, 29 patients (27.1%) had cirrhosis at baseline. Median follow-up was 79 months, and 70 patients (79.5%) reached biochemical response. Biochemical response was associated with reduced hazard of liver transplant or death (HR 0.07, 95% CI 0.01–0.46), whereas cirrhosis at diagnosis was an independent predictor of liver transplantation or death (Hazard ratio (HR) 11.8, 95%, confidence interval (CI) 1.18–117.4). Lack of normalization of serum IgG levels was associated with reduced 5-year transplant-free survival (95% in patients normalizing, compared to 86%, p  = 0.02). Conclusion: Normalization of serum IgG levels alone translates in better transplant-free survival in patients with AIH and should be a treatment target along with transaminases.